2019
DOI: 10.1111/liv.14044
|View full text |Cite
|
Sign up to set email alerts
|

Association between non‐alcoholic fatty liver disease and risk of atrial fibrillation in adult individuals: An updated meta‐analysis

Abstract: Background & Aims Recent studies examined the association between non‐alcoholic fatty liver disease (NAFLD) and risk of atrial fibrillation (AF) in adults, but the findings have been inconsistent. We provided a quantitative estimate of the magnitude of the association between NAFLD and risk of AF. Methods We searched publication databases using predefined keywords to identify observational studies (published up to December 14, 2018), in which NAFLD was diagnosed by biopsy, imaging or biochemistry and AF was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 49 publications
4
87
0
3
Order By: Relevance
“…Thirdly, we found an increased risk of developing cardiac arrhythmias such as AF and ventricular arrhythmias in NAFLD patients. The recent meta-analysis by Mantovani et al [38] involving 9 cross-sectional and longitudinal studies with a study sample of 364,919 subjects concluded that NAFLD was associated with an increased risk of AF in middle-aged and elderly subjects especially type 2 diabetics. Another meta-analysis assessing the relationship between NAFLD and AF conducted by Wijarnpreecha et al [39] involving 5 studies out of which 2 were cross-sectional studies and 3 were cohort studies with 238,129 participants concluded that NAFLD patients were at a significantly increased risk for developing AF compared to subjects without NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we found an increased risk of developing cardiac arrhythmias such as AF and ventricular arrhythmias in NAFLD patients. The recent meta-analysis by Mantovani et al [38] involving 9 cross-sectional and longitudinal studies with a study sample of 364,919 subjects concluded that NAFLD was associated with an increased risk of AF in middle-aged and elderly subjects especially type 2 diabetics. Another meta-analysis assessing the relationship between NAFLD and AF conducted by Wijarnpreecha et al [39] involving 5 studies out of which 2 were cross-sectional studies and 3 were cohort studies with 238,129 participants concluded that NAFLD patients were at a significantly increased risk for developing AF compared to subjects without NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, advancing age and increasing trends in risk factors in the US population may contribute to increased AF incidence and prevalence . AF and liver disease shared several common risk factors, resulting in more frequent presentation of AF in ELSD patients . This study also showed that risk factors for AF including hypertension, obesity, diabetes, dyslipidaemia, prior stroke and coronary artery disease in ESLD have increased over the period.…”
Section: Discussionmentioning
confidence: 57%
“…33 AF and liver disease shared several common risk factors, resulting in more frequent presentation of AF in ELSD patients. 36,37 This study also showed that risk factors for AF including hypertension, obesity, diabetes, dyslipidaemia, prior stroke and coronary artery disease in ESLD have increased over the period. Lastly, declining AF-related mortality in ESLD may also link to the increased AF prevalence.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, several observational studies reported an association between NAFLD and increased risk of AF in patients with and without T2D, after adjustment for multiple potential confounders [46]. A recent metanalysis showed that NAFLD was independently associated with increased risk of prevalent (OR 2.07) and, only in T2D patients, incident [hazard ratio (HR) 4.96] AF [47]. Studies investigating whether the reversal of NAFLD will reduce the risk of AF are eagerly awaited.…”
Section: Af and Vte In The Nafld Spectrummentioning
confidence: 99%